Computer Aided Design for Spray Driers - A. AI-Hemiri, Adil; N. Saleh, Saad (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The aim of this work is to develop an axi-symmetric two dimensional model based on a coupled simplified computational fluid dynamics (CFD) and Lagrangian method to predict the air flow patterns and drying of particles. Then using this predictive tool to design more efficient spray dryers. The approach to this is to model what particles experience in the drying chamber with respect to air temperature and humidity. These histories can be obtained by combining the particles trajectories with the air temperature/humidity pattern in the spray dryer. Results are presented and discussed in terms of the air velocity, temperature, and humidity profiles within the chambers and compared for drying of a 42.5% solids solution in a spray chamber 2.22m in diameter with a cylindrical top section 2.00m high and a bottom cone section 1.725m high.